Complex worlds from simpler nervous systems - Prete, Frederick R., 1948- (MIT Press, 2004)
The authors of Complex Worlds from Simpler Nervous Systems explain how animals with small, often minuscule, nervous systems--jumping spiders, bees, praying mantids, toads, and others--are not the simple "reflex machines" they were once thought to be. Because these animals live in the same world as do much larger species, they must meet the same environmental challenges. They do so by constructing complex perceptual worlds within which they can weigh options, make decisions, integrate unique experiences, apply complex algorithms, and execute plans--and they must do this with thousands rather than the billions of neurons necessary for their larger counterparts. The authors of each chapter, leading neuroscientists and animal behaviorists, present their research in ways that allow the reader to understand this process from the animal's perspective. The first of the book's three parts, "Creating Visual Worlds: Using Abstract Representations and Algorithms," examines the visual worlds of jumping spiders, honeybees, praying mantids, and toads. Part II, "Enhancing the Visual Basics: Using Color and Polarization," explores color vision and light polarization perception in honeybees, butterflies, crayfish, mantis shrimps, and octopuses. The final part, "Out of Sight: Creating Extravisual Worlds," examines the complex integration of visual and mechanosensory information in the cockroach and the unique auditory world of the unusual bladder grasshopper. All of these fascinating stories can be read both for what they teach us about the perceptual worlds of little animals, and for what they suggest about the general organizing principles of all central nervous systems, both "simple" and complex